Scoping carbon dioxide removal options for Germany–What is their potential contribution to Net-Zero CO2? - Borchers, Malgorzata; Thrän, Daniela; Chi, Yaxuan; Dahmen, Nicolaus; Dittmeyer, Roland; Dolch, Tobias; Dold, Christian; Förster, Johannes; Herbst, Michael; Heß, Dominik; Kalhori, Aram; Koop-Jakobsen, Ketil; et al. (Frontiers in Climate, 2022)
In its latest assessment report the IPCC stresses the need for carbon dioxide removal (CDR) to counterbalance residual emissions to achieve net zero carbon dioxide or greenhouse gas emissions. There are currently a wide variety of CDR measures available. Their potential and feasibility, however, depends on context specific conditions, as among others biophysical site characteristics, or availability of infrastructure and resources. In our study, we selected 13 CDR concepts which we present in the form of exemplary CDR units described in dedicated fact sheets. They cover technical CO2 removal (two concepts of direct air carbon capture), hybrid solutions (six bioenergy with carbon capture technologies) and five options for natural sink enhancement. Our estimates for their CO2 removal potentials in 2050 range from 0.06 to 30 million tons of CO2, depending on the option. Ten of the 13 CDR concepts provide technical removal potentials higher than 1 million tons of CO2 per year. To better understand the potential contribution of analyzed CDR options to reaching net-zero CO2 emissions, we compare our results with the current CO2 emissions and potential residual CO2 emissions in 2050 in Germany. To complement the necessary information on technology-based and hybrid options, we also provide an overview on possible solutions for CO2 storage for Germany. Taking biophysical conditions and infrastructure into account, northern Germany seems a preferable area for deployment of many concepts. However, for their successful implementation further socio-economic analysis, clear regulations, and policy incentives are necessary.